Is returning to work during the COVID-19 pandemic stressful? A study on immediate mental health status and psychoneuroimmunity prevention measures of Chinese workforce - Tan, Wanqiu; Hao, Fengyi; McIntyre, Roger S.; Jiang, Li; Jiang, Xiaojiang; Zhang, Ling; Zhao, Xinling; Zou, Yiran; Hu, Yirong; Luo, Xi; Zhang, Zhisong; Lai, Andre; et al. (Brain, behavior, and immunity, 2020)
•The psychological effects of returning to work during the COVID-19 pandemic is unknown.•10.8% of respondents suffered from post-traumatic stress disorder after returning to work.•Returning to work had not caused a high level of psychiatric symptoms in the workforce.•Psychoneuroimmunity prevention measures were associated with less psychiatric symptoms.•More executives practiced hand hygiene and more workers avoided sharing utensils.•Psychoneuroimmunity measures of the Chinese workforce can be applied to other countries. This study aimed to quantify the immediate psychological effects and psychoneuroimmunity prevention measures of a workforce returning to work during the COVID-19 epidemic. Workforce returning to work was invited to complete an online questionnaire regarding their attitude toward the COVID-19 epidemic and return-to-work along with psychological parameters including the Impact of Event Scale-Revised, Depression, Anxiety, Stress Scale- 21 (DASS-21) and Insomnia Severity Index (ISI). Psychoneuroimmunity prevention measures include precautions at personal and organization levels. From 673 valid questionnaires, we found that 10.8% of respondents met the diagnosis of post-traumatic stress disorder (PTSD) after returning to work. The respondents reported a low prevalence of anxiety (3.8%), depression (3.7%), stress (1.5%) and insomnia (2.3%). There were no significant differences in the severity of psychiatric symptoms between workers/technicians and executives/managers. >95% reported psychoneuroimmunity prevention measures including good ventilation in the workplace and wore a face mask as protective. Factors that were associated with the severity of psychiatric symptoms in the workforce were marital status, presence of physical symptom, poor physical health and viewing return to work as a health hazard (p < 0.05). In contrast, personal psychoneuroimmunity prevention measures including hand hygiene and wearing face masks as well as organizational measures including significant improvement of workplace hygiene and concerns from the company were associated with less severe psychiatric symptoms (p < 0.05). Contrary to expectations, returning to work had not caused a high level of psychiatric symptoms in the workforce. The low prevalence of psychiatric symptoms could be due to confidence instilled by psychoneuroimmunity prevention measures before the resumption of work. Our findings would provide information for other countries during the COVID-19 pandemic.